Potensi Aktivitas Anti-Tuberkulosis Ekstrak Daun Pegagan (Centella Asiatica L. Urban) dalam Menghambat Pertumbuhan Mycobacterium Tuberculosa - Tri Anti Permata Sari (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Tuberculosis (TB) still remains a disease that causes health issues in society. TB is a direct infectious lung disease caused by the TB germ (Mycobacterium tuberculosis) which is also known as acid-fast bacteria (AFB). A survey conducted by the World Health Organization (WHO) around the world states that up to there are 9,000,000 incidents of cases and 1.5 million people died from TB, therefor TB is ranked as the 10th highest cause of death in the world. Indonesia itself ranks two of the most TB cases in the world. This paper aims to determine the potential and effectiveness of Gotu kola leaf extract as an anti-tuberculosis in inhibiting the growth of Mycobacterium. This research method is to review the articles with the keywords tuberculosis, Gotu kola leaves, Mycobacterium tuberculosis, and anti-tuberculosis. The data show that giving Gotu kola leaf extract can significantly reduce the growth of Mycobacterium tuberculosis because Gotu kola leaves contain bioactive compounds that have anti-mycobacterial activity. The consumption of Gotu kola leaves together with TB medication is not dangerous and does not cause side effects, actually, Gotu kola leaves provide a hepatoprotective effect against the hepatotoxic effects caused by medication of TB. Gotu kola leaves also have the ability to increase the body's immune response because it is rich in antioxidants and can prevent lung tissue damage due to TB infection.